Nasolabial outcomes in a nationwide study of orofacial cleft in New Zealand. (29th March 2019) - Thompson, John M. D.; Stone, Peter R.; Williams, Kirk; Sanders, Megan; Mason, Nicki; Pope, Rodney; Fowler, Peter V.
Structured Abstract: Objectives: To (a) assess nasolabial outcomes across four main cleft subgroups, (b) assess agreement using a categorical and a continuous scoring measure and (c) compare outcomes to international studies. Settings and Sample Population: Analysis of 470 images of which 218 was unilateral cleft lip and palate (UCLP), 128 unilateral cleft lip (UCL), 90 bilateral cleft lip and palate (BCLP) and 34 bilateral cleft lip (BCL). Images were taken around five (n = 279) and eight‐ten (n = 191) years of age. Materials & Methods: Cropped images were assessed using the Asher‐McDade (AM) and a 100 mm visual analogue scale (VAS) by a panel of six raters. Scoring was undertaken for vermillion border and nasal form, symmetry and profile. Analysis was undertaken for each subscore, a total score with sensitivity analysis using a total score based on the subscores for each patient. AM intra‐ and inter‐rater reliability was assessed using weighted kappa and for the VAS components reliability was assessed using Pearson correlation. Results: The AM intra‐rater reliability was moderate/substantial, whilst inter‐rater reliability was fair. The VAS intra‐rater correlations were high, and inter‐rater correlations were moderate. Better outcomes were found with cleft lip (CL) vs cleft lip and palate (CLP). No differences were found for sex, ethnicity, age and cleft laterality (unilateral). The AM found no difference between unilateral or bilateral. The VAS found bilateral scored worse than unilateral for both CL and CLP. Conclusions: The nasolabial outcomes differ by cleft type. The correlation was relatively high for the VAS whilst the AM had relatively poor reliability.